Методика проведения натурных наблюдений за процессами деформации (абразии) коренных берегов водохранилищ Беларуси - Kobyak, Валерий; Kukshinov, Михаил (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2011)
Lowland water-storage basins in Belarus are established. The types and frequency of field observations over deformation of banks are identified. The choice for identification of potentially dangerous areas prone to abrasion processes with their partition into control ranges and diameters is offered. The method for field studies of deformation processes (abrasion) of loose banks at water-storage basins of Belarus is presented.